BALLONS AND BUTEYKO BLOWING EXERCISES AGAINST PEAK CURRENT EXPIRATION OF ASTHMA PATIENTS - Ihwan, Anhar; Nugraha, Ary; Negara, Candra Kusuma (Sean Institute, 2022)
Asthma is becoming a serious global health problem and needs to be addressed. Many asthmatics from various countries experience asthma disorders, so if it is not controlled, it can increase the morbidity rate. One way to assess the occurrence of asthma is to conduct an Expiratory Peak Current (APE) assessment. Do Buteyko breath exercises and Blowing Balloons to overcome and alleviate asthma symptoms. This study aimed to compare Buteyko's breath exercises with Blowing Balloons exercises against changes in peak expiratory currents in asthma patients. The research design used was quasi-experimental with pretest and post-test methods in two groups. The study sample of 20 respondents consisted of 2 groups, namely 10 respondents of the Buteyko breath exercise group and 10 respondents of the Blowing Balloons exercise group, with a simple random sampling technique. After Buteyko breath training and Blowing Balloons exercises were carried out 2 times a day for two weeks, the Wilcoxon sign rank test results for Buteyko breath training and Blowing Balloons exercises with a value of p = 0.00 were obtained. The results of the Mann withney test showed no difference in the mean rank of the asthma control test (ACT) score in Buteyko's breath exercise and Blowing Balloons exercise p = 0.21. The results of measuring the expiratory peak current (APE) showed a significant difference with the p-value = 0.00 in Buteyko breath exercises and Blowing Balloons exercises. Based on the study's results, it can be concluded that Buteyko's breath exercises and Blowing Balloons exercise positively impact the management of asthma symptoms. The results of this study can be an input for nursing services to be used as a guideline for developing Buteyko's breath exercises by blowing balloons against peak expiratory currents in asthma patients integrated into the provision of nursing care.